2005
DOI: 10.1172/jci22833
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal synthesis of oligoclonal IgM against myelin lipids predicts an aggressive disease course in MS

Abstract: Oligoclonal IgM bands restricted to cerebrospinal fluid are an unfavorable prognostic marker in MS, the most common demyelinating disease of the CNS. We have attempted to identify the B cell subpopulation responsible for oligoclonal IgM secretion and the specificity of these bands. In addition, we explored the relationship between specificity and disease evolution. Intrathecal B cell subpopulations present in 29 MS patients with oligoclonal IgM bands and 52 without them were analyzed. A considerable increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(141 citation statements)
references
References 43 publications
8
130
3
Order By: Relevance
“…These authors failed to demonstrate Toxoplasma gondii-specific fLC in AIDS patients with T. gondii encephalitis using IEF/AIB:although o-fLC were found in all patients; antigen-specific fLC were demonstrated by ELISA instead. The way Villar et al described CSF-restricted lipid-specific oligoclonal IgM bands 57 , we can speculate whether CSF-restricted fLC could have the same specificity.…”
Section: Discussionmentioning
confidence: 81%
“…These authors failed to demonstrate Toxoplasma gondii-specific fLC in AIDS patients with T. gondii encephalitis using IEF/AIB:although o-fLC were found in all patients; antigen-specific fLC were demonstrated by ELISA instead. The way Villar et al described CSF-restricted lipid-specific oligoclonal IgM bands 57 , we can speculate whether CSF-restricted fLC could have the same specificity.…”
Section: Discussionmentioning
confidence: 81%
“…22 CSF IgM OCBs can also be found in a subset of patients with pediatric-and adult-onset MS. In adults their presence has been associated with more active/ aggressive disease, 23 but such an association has not been established in pediatric MS. 24 Of note, CSF exhibits age-related changes independent of MS disease mechanisms, particularly around puberty. Reiber et al 20 showed that the amount of intrathecal IgG doubles during puberty because of an increase in the albumin quotient, which represents normal physiologic growth.…”
Section: General Aspects Of Cns Inflammatory Demyelinating Diseases Mmentioning
confidence: 99%
“…Binding of OCBs was investigated by immunoblotting with a phosphatase alkaline anti-human IgG Ab for 2h30 (Jackson ImmunoResearch Laboratories, Suffolk, U.K.). OCB reactivity was then explored as described previously (18). Patients were considered as negative when they lacked bands in the SPAG16 blot or showed the same pattern in the SPAG16 and THIO (control) membranes.…”
Section: Isoelectric Focusingmentioning
confidence: 99%